PENGARUH PERSEPSI PENGEMBANGAN KARIER DAN FEAR OF SUCCESS TERHADAP KESEJAHTERAAN PSIKOLOGIS POLISI WANITA DI MAPOLDA DIY - Estikomah (Wahana Islamika: Jurnal Studi Keislaman, 2018)
As a law enforcement agency in Indonesia, the police mustshow good performance. In order to maintain and improve theperformance of the police, the support of all personnel is indispensable,with the exception of the Policewomen. Policewomen performance willbe good if they have good psychological well-being, so researchingvariables that can affect psychological well-being is very important.Based on this, this study aims to examine the effect of fear of successcareer development on the psychological well-being of Policewomen inMapolda DIY This study uses a quantitative approach with the numberof research subjects amounting to 137 consisting of Policewomen inMapolda DIY. The analysis method used in this study is multiplelinear regression analysis. The results of the study found that theperception of career development and fear of success had a positive andsignificant influence on psychological well-being. In addition, thisstudy also found that the perception of career development has a greaterinfluence on psychological well-being compared to the influence givenby fear of success on psychological well-being.